Symmetries in noncommutative field theories: Hopf versus Lie (The São Paulo Journal of Mathematical Sciences, 2010)
I discuss motivations for introducing Hopf algebra symmetriesin noncommutative eld theories and briey describe twisting ofmain symmetry transformations. New results include an extended listof twisted gauge invariants (which may help to overcome the problemof inconsistency of equations of motion) and a gauge-covariant twistoperator (leading to a gauge-covariant star product).MSC: 81T75, 70S10